(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the relationship between Arab media and Arab identity, and to analyze the role of media in either reinforcing or weakening the components of identity in light of contemporary media transformations, particularly media globalization and the growing influence of satellite and digital media as well as social networking platforms. The study adopts a descriptive-analytical approach based on reviewing and analyzing relevant theoretical literature and previous studies on media and cultural identity. The findings indicate that Arab media plays a dual role in shaping Arab identity. On one hand, certain media discourse contributes to strengthening the Arabic language, cultural values, and a sense of cultural belonging. On the other hand, media discourse influenced by foreign media models contributes to marginalizing some elements of Arab identity and weakening their presence, especially among youth. The study also reveals that digital transformations and media globalization have intensified the complexity of the relationship between media and identity, creating cultural challenges that require conscious and strategic media approaches. The study recommends developing Arab media discourse, enhancing purposeful cultural content, supporting the use of standard Arabic, and positively employing digital media to protect and reinforce Arab identity within collective cultural awareness.